(untitled) (Bulletin KNOB, 2004)
Since the middle of the fifteenth century the name of Jesus is increasingly found on buildings and other objects. This pious custom was encouraged by the Observants, in this case the preachers of the Franciscan monastic order and was later taken over by the Jesuits. The initiative was taken by Bernardinus of Siena (1380-1444), who was canonized in 1450. After his sermon the letters IHS were applied to the town hall of Siena in 1425, where they are still to be seen. The application of the name of Jesus to the town halls of Deventer and Zwolle in 1458 and 1455 respectively was related to the fact that the magistrate heard the sermons of the priest Jan Brugman, a member of the same monastic order and propagator of the ideas of Bernardinus in the north of the Netherlands. Penitential preachers encouraged public burning of sinful and vain objects, tried to bring about peace and forgiveness, among other things by abolishing party blazon in order to make room for the name of Jesus. Besides a series of examples in Italy we know the IHS-monogram of a house in Kampen, the monastery in Ter Apel and especially a lot of houses in the town of Munster, frequently also in connection with abbreviations of the names of Maria and John. The name of Jesus furthermore occurs on chairs, clocks, mantelpieces, ceramics, written contracts, stained glass windows and other items of everyday use. Buildings at the background of the scenes in remembrance of the sermons of penitential preachers (Siena, Bamberg) are accurately represented. This was the visible outside world, whereas religious themes were often situated in the houses, or likewise souls, of the just as realistically portrayed commissioners, a place where ‘... onse lieve gheminde Heer tot ons ende van ons sal segghen: dit sal myn ruste wesen in ewicheyt der ewicheyt’ (our dear beloved Lord until our end will say of us: this will be my peace in eternity of eternity). Medieval man was concerned about the active presence of Jesus in daily life. This was also expressed in applying the IHS-monogram ‘... opdat hy sijn wapen sye in onser woeninghe; want overmids die wapen pleghet men te kennen der heren woeninghen’ (that he may see his blazon in our dwellings; for by this blazon one will recognize the dwellings of the Lord).